Escenarios de producción de energía eléctrica en una pequeña central hidroeléctrica utilizando series sintéticas. - Carrillo Carrillo, Manuel Francisco (2023)
The present research work proposes the use of a mathematical model for the projection of the production of electrical energy of the ILLUCHI II hydroelectric power station, based on the importance that the study of the future behavior of energy for the local population brings with it. The ARIMA model is used, with the data provided by the Cotopaxi electric company (ELEPCO S.A). The historical data address the energy production from the year 2018 to the year 2022, which allow generating a refined Excel database, consequently starting the creation of the algorithm and its coding in Jupiter Notebook, by calling the different libraries that provides such software.